A Review On Design Parameters Of Hand-Operated Product That Influence Hand Grip Of Senior Citizen - Halim, Isa; Padmanathan, Vinothini; Radin Umar, Radin Zaid; Saptari, Adi (Penerbit UTHM, 2020)
The number of senior citizens worldwide is growing and therefore ergonomically designed handoperated products are necessities and play a vital role in their everyday lives. However, designing hand-operated products for senior citizen users pose distinct challenges because the design parameters are different from the young adults’ requirements. Some senior citizens are vulnerable to hand-related diseases such as arthritis, stroke or impairment of the motor and Parkinson that can limit them to carry and hold hand-operated products. The aim of this paper is to present a comprehensive overview of design parameters of hand-operated products that influence hand grip of senior citizens. The authors searched the information of design parameters from journal articles, conference proceedings, doctoral dissertations and guidelines from online databases such as Google Scholar, ScienceDirect and Pubmed. The following keywords were used throughout the search: hand-operated products; hand grip; hand dexterity; product weight; product shape; product contact surface; grip span; force and torque requirements; handle diameter, length and orientation; product size; product materials; spring stiffness. Based on review of 140 journal articles, six main design parameters of hand-operated products were identified to influence hand grip of senior citizens. The design parameters can be categorized as: 1) weight; 2) shape, grip span, size; 3) materials, contact surface, friction coefficient; 4) force, torque and spring stiffness; 5) diameter, length and orientation of handle; 6) clearance or allowance. These parameters met the principles of ergonomic designs that allow senior citizens to operate hand-operated products with neutral wrist posture, less muscle effort and ease of use.